Nanoplankton assemblages in maritime Antarctic lakes: characterisation and molecular fingerprinting comparison - Unrein, Fernando; Izaguirre, Irina; Massana, Ramon; Balagué, Vanessa; Gasol, Josep M. (Aquatic Microbial Ecology, 2005)
14 pages, 3 figures, 4 tables The composition of planktonic eukaryotes in the size fraction 3-20 μm of 10 maritime Antarctic lakes was studied by denaturing gradient gel electrophoresis (DGGE). Microscopic observations were also carried out to compare the results obtained by this molecular fingerprinting technique with morphological data. Six lakes from Hope Bay (Antarctic Peninsula) and 4 from the Potter Peninsula (King George Island) were sampled during the austral summer of 2003. These lakes were of different trophic status and covered a wide range of limnological features. Previous studies of the planktonic communities of these lakes revealed high nanoflagellate abundance and biomass, but their taxonomic identification was usually uncertain due to their similarity in size and shape. Here, the application of DGGE allowed both a comparison of the structure of the nanoplanktonic communities and an identification of the dominant populations through sequencing of the most prominent DGGE bands. The most important organisms in these lakes were the Chrysophyceae, represented in the DGGE gel by 5 different band positions and identified by microscopy in 5 different morphotypes, including uniflagellated and biflagellated naked organisms: 1 sequence belonged to the Chrysosphaerales, 2 closely related bands (likely 2 species from the same genus) belonged probably to the Ochromonadales (unicellular biflagellates), while the other 2 bands could not be assigned to any defined chrysophyte group. Sequences related to Chlorophyceae, Bacillariophyceae and probably Cercozoa were also retrieved. A Dictyochophyceae belonging to the order Pedinellales is reported for the first time in freshwater Antarctic ecosystems. Microscopic observations suggest that this phytoplanktonic organism most likely corresponds to Pseudopedinella. Most of the lakes shared several common sequences, such as 2 chrysophyte bands, which suggests the existence of well-adapted nanoplanktonic species dispersed throughout the Antarctic lakes. However, some ...